2018
DOI: 10.1080/02640414.2018.1559972
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Challenge Tour golfers’ clubhead velocity and force producing capabilities during a countermovement jump and isometric mid-thigh pull

Abstract: 21A number of field-based investigations have evidenced practically significant relationships 22 between clubhead velocity (CHV), vertical jump performance and maximum strength. 23Unfortunately, whilst these investigations provide a great deal of external validity, they are 24 unable to ascertain vertical ground reaction force (vGRF) variables that may relate to golfers' 25 CHVs. This investigation aimed to assess if the variance in European Challenge Tour golfers' 26 CHVs could be predicted by countermovement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…During all golf shots, subjects rated each shot 1 to 5; with 5 being the best strike. Any ratings of 1 and 2 were excluded and additional shots were performed, up to a maximum of 12 shots with each golf club (33). All golf shots were struck from a rubber tee placed on an artificial golf mat fixed to the floor in the center of the golf bay.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…During all golf shots, subjects rated each shot 1 to 5; with 5 being the best strike. Any ratings of 1 and 2 were excluded and additional shots were performed, up to a maximum of 12 shots with each golf club (33). All golf shots were struck from a rubber tee placed on an artificial golf mat fixed to the floor in the center of the golf bay.…”
Section: Methodsmentioning
confidence: 99%
“…During each golf shot, subjects were instructed to perform their standard golf swing with the aim of maximizing distance and accuracy. Subjects were instructed to aim towards a target area in the middle of the range (28,33). All subjects used their own driver and 7-iron for the golf shots during testing and all subjects wore appropriate golf shoes (2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has then resulted in a more thorough analysis of the correlation between CHV and jump performance resulting in stronger relationships such as concentric impulse during the countermovement jump (CMJ) and CHV. 5,6 In a similar manner lower body strength has a wide array of assessment techniques again leading to inconsistent findings as to the strength of the relationship between lower body strength relates to CHV. As the golf swing is performed quickly, especially the downswing which is the phase of the swing where clubhead acceleration occurs, it has been suggested that the isometric midthigh pull (IMTP) would provide a more sport-specific assessment over the traditional 1-repetition maximal (1RM) testing.…”
Section: Introductionmentioning
confidence: 99%